Um olhar sobre técnicas de demonstração matemática em sala de aula na educação básica - Pimentel, José Laécio (Universidade Federal Rural do Semi-Árido, 2018)
The present dissertation had the general objective to take a look at mathematical demonstration techniques in the classroom in Basic Education. This work began with a bibliographical research and was based on authors such as Fiorentini (1994), D'Ambrosio (2007), Fossa (2009), Pinedo (2011), Hausen (2013) and Caputi and Miranda 2017). A qualitative research was carried out, in which the data were collected from five questions of an interview applied to ten mathematics teachers from eight public schools in the state of Ceará, with an emphasis on Basic Education. Given the relevance and scope of the topic, it is considered that there is much to be addressed in this regard. After all, demonstrating a proposition in mathematics requires experience, for there are rules and techniques that are fundamental in this task. This is also an effective way to promote learning in Basic Education. It has been proven, therefore, that this content is reasonably used in classes at this educational stage. The data revealed that teachers are aware that mathematical demonstration techniques could contribute in a more productive and meaningful way if they were used more widely in different classes and levels of education. To think that the subject under study is a high school and very advanced for basic education, is a misconception. It was observed throughout the research that teachers are in tune with the relevance of including and/or using some technique of mathematical demonstration in Basic Education. Thus, they also said that they use it when it is relevant, but they do not do it more often because they observe that their students present limitations of understanding in relation to some basic mathematical knowledge. It is concluded that teachers and the school curriculum need and should make use of mathematical demonstration techniques to make teaching and learning more effective in producing knowledge by stimulating the students' minds, using the contents and different learning methodologies. productive, meaningful and efficient
Keywords: Técnicas de demonstração matemática; Aprendizagem; Educação Básica; Parâmetros Curriculares Nacionais do Ensino Médio; Mathematical demonstration techniques; Learning; Basic education; National Curricular Parameters of High School; CIENCIAS EXATAS E DA TERRA::MATEMATICA